Single-molecular phosphorus phthalocyanine-based near-infrared-II nanoagent for photothermal antitumor therapy. Issue 38 (12th June 2020) - Zhou, Li-Na; Pan, Houhe; Kan, Jing-Lan; Guan, Qun; Zhou, Yang; Dong, Yu-Bin
Abstract : A molecular phosphorus phthalocyanine (P-Pc )-based nanoagent P-Pc-HSA, which can be a highly efficient NIR-II antitumor agent, is reported. Abstract : As one of the noninvasive cancer treatments, photothermal therapy (PTT) has drawn intense attention recently. In this context, an important task is to explore novel and versatile nanoscale photothermal agents (PTAs), especially those with strong NIR-II light absorption, high photothermal conversion efficiency, good photostability and biocompatibility. Phthalocyanines (Pcs), as the second-generation photosensitizers, are a promising class of candidates for PTT due to their strong NIR absorption and high photothermal conversion efficiency. However, the poor water solubility severely limited their application as PTAs in tumor treatment. Herein, we report a molecular phosphorus phthalocyanine (P-Pc )-based nanoagent via incorporation of human serum albumin (HSA) under mild conditions. The obtained nanoscale P-Pc-HSA possesses excellent photothermal conversion efficiency (64.7%) upon 1064 nm light irradiation, furthermore, it can be a highly efficient NIR-II antitumor nanoagent via photothermal treatment (PTT), which is fully evidenced by the in vitro and in vivo experiments.